Addressing the Employment Effects of the Financial Crisis : The Role of Wage Subsidies and Reduced Work Schedules - Robalino, David; Banerji, Arup (World Bank, Washington, DC, 2012)
This note briefly reviews the experiences with wage subsidies and reduced work schedules in promoting employment and avoiding the depreciation of accumulated skills and knowledge due to a temporary downturn. These policies have been adopted by many high income countries as well as some middle income countries. It is to early o comment on their impact; to date, they have not been rigorously evaluated in the context of the financial crisis. And any results will also be difficult to generalize, since much depends on local conditions and the structure of the labor market. Wage subsidies and reduced work schedules show some promise as measures that can help countries to increase the employment elasticity of growth during the recovery and avoid the depreciation of skills associated with unemployment or informal work. Wage subsidies and reduced work schedules mainly benefit formal sector workers, which represent less than 50 percent of the labor force in most middle and low income countries.